Suggested Mechanisms of Tracheal Occlusion Mediated Accelerated Fetal Lung Growth: A Case for Heterogeneous Topological Zones - Marwan, Ahmed I.; Shabeka, Uladzimir; Dobrinskikh, Evgenia (Frontiers in Pediatrics, 2018)
In this article, we report an up-to-date summary on tracheal occlusion as an approach to drive accelerated lung growth and strive to review the different maternal and fetal derived local and systemic signals and mechanisms that may play a significant biological role in lung growth and formation of heterogeneous topological zones following tracheal occlusion. Pulmonary hypoplasia is a condition whereby branching morphogenesis and embryonic pulmonary vascular development are globally affected and is classically seen in congenital diaphragmatic hernia. Tracheal occlusion is an innovative approach aimed at driving accelerated lung growth in the most severe forms of diaphragmatic hernia and has been shown to result in improved neonatal outcomes. Currently, most research on mechanisms of tracheal occlusion induced lung growth is focused on mechanical forces and is viewed from the perspective of homogeneous changes within the lung. We suggest that the key principle in understanding changes in fetal lungs after tracheal occlusion is taking into account formation of unique variable topological zones. Following tracheal occlusion, fetal lungs might temporarily look like a dynamically changing topologic mosaic with varying proliferation rates, dissimilar scale of vasculogenesis, diverse patterns of lung tissue damage, variable metabolic landscape, and different structure. The reasons for this dynamic topological mosaic pattern may include distinct degree of increased hydrostatic pressure in different parts of the lung, dissimilar degree of tissue stress/damage and responses to this damage, and incomparable patterns of altered lung zones with variable response to systemic maternal and fetal factors, among others. The local interaction between these factors and their accompanying processes in addition to the potential role of other systemic factors might lead to formation of a common vector of biological response unique to each zone. The study of the interaction between various networks formed after tracheal occlusion (action of mechanical forces, activation of mucosal mast cells, production and secretion of damage associated molecular pattern substances, low-grade local pulmonary inflammation, and cardiac contraction induced periodic agitation of lung tissue, among others) will bring us closer to an appreciation of the biological phenomenon of topological heterogeneity within the fetal lungs.